LL-EXIT 2015 : Kunsthappening. - Elias, Willem (Antwerpen : De vrienden van HVV vzw, 2015)
De Vos, Kasper ; Vandoorne, Vera ; De Buyser, Jeanne ; Wens, Kobe ; Kegels, Jeroen ; De Clercq, Pieter ; Le Bruyn, Gitte ; Van Parys, Simon ; Poilvet, Gilles ; Scheir, Katrien ; Kerkhove, Naomi ; van Parys, Domien ; Zovko, Sanja
LL-EXIT 2015, Karel Cuypershuis, Roermond, 2015
boek